2016
DOI: 10.2166/wp.2016.021
|View full text |Cite
|
Sign up to set email alerts
|

The role of proximity in problem identification: risk of water scarcity in Texas

Abstract: This project seeks to determine whether proximity to major water sources (e.g. rivers or lakes) is associated with the public's perception of water scarcity. From a theoretical perspective, this project will aid our collective understanding of problem identification. From a practical perspective, this relationship could help inform decision makers about where support or resistance to a water policy may be concentrated and allow more targeted efforts to help inform citizens about short- and long-term water poli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…One way to address this issue is through utilizing a multidimensional approach: one that considers both social issues (e.g., abortion) and economic issues (e.g., fiscal policy; Barnett, Öz, & Marsden, ; Everett, ). Similar limitations are found in studies of environmental attitudes, which often utilize brief unidimensional measures (Kitamura, Mokhtarian, & Laidet, ) or only addressing issues relating to one specific event (Mahafza, Stoutenborough, & Vedlitz, ; Wang, Lee, & Polonsky, ). Researchers have attempted to create a valid, standardized measure of environmental attitudes (Dietz, Stern, & Guagnano, ; Dunlap & Jones, ; Milfont & Duckitt, ), as there was still a lack of consensus with operationalizing key concepts (Heberlein, ), and measuring environmentalism as a latent construct, rather than observed.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…One way to address this issue is through utilizing a multidimensional approach: one that considers both social issues (e.g., abortion) and economic issues (e.g., fiscal policy; Barnett, Öz, & Marsden, ; Everett, ). Similar limitations are found in studies of environmental attitudes, which often utilize brief unidimensional measures (Kitamura, Mokhtarian, & Laidet, ) or only addressing issues relating to one specific event (Mahafza, Stoutenborough, & Vedlitz, ; Wang, Lee, & Polonsky, ). Researchers have attempted to create a valid, standardized measure of environmental attitudes (Dietz, Stern, & Guagnano, ; Dunlap & Jones, ; Milfont & Duckitt, ), as there was still a lack of consensus with operationalizing key concepts (Heberlein, ), and measuring environmentalism as a latent construct, rather than observed.…”
Section: Introductionmentioning
confidence: 76%
“…One way to address this issue is through utilizing a multidimensional approach: one that considers both social issues (e.g., abortion) and economic issues (e.g., fiscal policy; Barnett, Öz, & Marsden, 2018;Everett, 2013). Similar limitations are found in studies of environmental attitudes, which often utilize brief unidimensional measures (Kitamura, Mokhtarian, & Laidet, 1997) or only addressing issues relating to one specific event (Mahafza, Stoutenborough, & Vedlitz, 2017;Wang, Lee, & Polonsky, 2018).…”
Section: The Current Studymentioning
confidence: 99%
“…2004; Mahafza et al . 2017). Similarly, we found that higher water cover was associated with a greater perception of water‐quality problems, but a lower perception of other environmental problems, suggesting water cover (and in some cases streams specifically) may also improve perceptions of one's broader environment.…”
Section: Discussionmentioning
confidence: 99%
“…Following DeBoer, this study utilizes Google Map software to calculate the driving distance between target firm and the central point of the major city, the driving distance could reflect the accessibility and convenience of communication between socio-economic entities (Husted et al, 2016;DeBoer et al, 2017). Based on the operational definition from Mahafzaa (Mahafza et al, 2017), we adopt the logarithm of the driving distance between the firm's location and the city center point as the measurement of proximity to major cities. Also, in case that the target firm's distance to the central point is less than 1 km, we increase all the measured distance by 1 km before taking the logarithm (Broekel and Boschma, 2011).…”
Section: Methodsmentioning
confidence: 99%